Effect of GR24 concentrations on biogas upgrade and nutrient removal by microalgae-based technology. (September 2020) - Shen, Xiaoxiao; Xue, Zhaoxia; Sun, Li; Zhao, Chunzhi; Sun, Shiqing; Liu, Jinhua; Zhao, Yongjun; Liu, Juan
Graphical abstract: Highlights: Strigolactone (GR24) had positive effects on microalgae growth. The optimal GR24 concentration was between 10 −9 and 10 −7  M. Nutrient removal efficiencies were more than 75% under GR24 induction. GR24 significantly improved photosynthetic performance of C. vulgaris . Abstract: Freshwater microalgae Chlorella vulgaris was cultured and induced with strigolactone (GR24) to simultaneously eliminate nutrients in biogas slurry and purify biogas. Treatment with 10 −7  M GR24 yielded maximum growth rate and mean daily productivity for algae at 0.187 ± 0.06 d −1 and 0.097 ± 0.008 g L −1  d −1, respectively. Results from chlorophyll fluorescence transients method demonstrated that moderate concentration of GR24 could enhance the photosynthetic performance of microalgae. In addition, GR24 affected intracellular carbonic anhydrase activity and chlorophyll-a content. Maximum chemical oxygen demand, total nitrogen, and CO2 removal efficiencies were 78.62 ± 2.36%, 76.47 ± 1.53% and 64.05 ± 1.15% with 10 −7  M GR24 induction, respectively. Further, highest total phosphorus removal efficiency (80.27 ± 1.93%) was observed at 10 −9  M. The optimal GR24 concentration range was determined to be between 10 −9 and 10 −7  M in consideration with nutrient and CO2 removal efficiencies.